Essays on the Economics of Energy and Real Estate Management - (:unkn) unknown (My University, 2025)
This thesis analyzes the economics of energy and real estate management by means of three essays. First, I analyze a large real estate portfolio in Switzerland to quantify the effects of energy efficiency improvements on energy consumption and rents. Applying a difference-in-difference identification strategy, I provide novel evidence on the potential contribution of energy efficiency as an emissions mitigation strategy. Second, I elicit Swiss homeowners' investment behavior related to alternative space heating, including energy efficient and renewable technologies. Using an experimental design combining within and between variations, I quantify how the provision of information about CO2 emissions and CO2 taxes affects decisions. Finally, I assess Swiss tenants' preferences for alternative heating technologies in terms of their willingness to trade-off lower energy bills and higher rents. I apply the Multiple Price List procedure and assess how the acceptability of renovation strategies is affected by information on CO2 emissions and CO2 taxes. Overall, this thesis will provide novel insights on the behavioral and welfare effects associated with energy efficiency improvements in residential buildings.
Keywords: Residential energy consumption; energy efficiency; energy efficiency gap; investment behavior; building retrofits; alternative heating.